Role of DUF1727 domain in the amidation of peptidoglycan of Staphylococcus Aureus - Lobo, Ricardo André Santos (2015)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014